RUMPANGNYA PENGUATAN PENDIDIKAN KARAKTER DI TENGAH GAP GENERASI - Mufti Riyani; Asnawi Asnawi; Hanafiah Hanafiah; Rapita Aprilia; Aulia Rahman (Universitas Muria Kudus, 2023)
The aims of this research are 1). prove the characteristics of Generation Z as the subject of character education, between theory and facts in the field, 2). find the possibility to reduce the gap between generations and unify the vision of character education, 3). formulate solutions and methods that can be applied so that the implementation of character education in schools can be more effectiveThe research method used is qualitative with phenomenology type. Methods of data collection using observation, interviews and questionnaires. The subjects of your research were junior high school students from several schools in Langsa City, Aceh and the border areas of North Sumatra. The informants who participated in this study were 44 students. Coming from 3 schools namely SMPN 2 Langsa, SMPN 3 Langsa and SMPN 1 Babalan, North Sumatra. The research was conducted in May 2021. The data validity technique used source triangulation and interactive analysis was used as a data analysis technique.The results of this study indicate that the characteristics of Generation Z are not fully owned by children in their early teens in research settings. In some cases, differences in character and values between teachers and students become obstacles to strengthening character education. Integrity character is the weakest character. Barriers to social relations in the development of Generation Z are caused by the fact that they are in the stage of finding their own identity and characteristics. In this situation, the teacher can take the role of guiding and providing support so that there is no gap between generations which results in culture shock between the teacher and student relationship. The initial conditions of the Z generation can be used as a reference for determining teacher efforts in obtaining keys in interpersonal relations with students and building an atmosphere that supports strengthening character education